Optimum Conditions Of 5-Nucleotidase Activity In Sera Of KalaAzaric Patients. - AL-Rubaee, Eaman A.S. (Journal of the Faculty of Medicine Baghdad, 2006)
Background: This research focuses on the characterization studies of 5v-Nucleotidase (5'-NT) of kalaazar patients' sera. 5V NT is one of the enzymes used as indicator of liver function test . In this study the optimum conditions for the activity of 5s - NT enzyme has been demonstrated for kalaazaric patients.Materials and methods: Thirty five blood samples were obtained from Baghdad Hospitals from untreated infants and children with kala-azar. 5'-NT activity was measured by following themethod of Wood and Williams.Results: Optimum conditions of serum 5' - NT activity of kala- azaric patients obtained were 50 u L , 30 minutes ,0.8 mM,7.7 and 50'C) as (Volume of serum , incubation time , substrateconcentration, pH and temperature) respectively